Patient safety in the face of the COVID-19 pandemic: theoretical-reflective essay (Research, Society and Development, 2020)
Objective: to reflect on actions related to patient safety in the pandemic. Methodology: theoretical-reflective essay, produced from the critical analysis of national and international literature on patient safety in the new Coronavirus pandemic. Results: the pandemic has been reflected in several sectors of society and, consequently, in patient care. As actions related to patient safety in the face of the new Coronavirus, used and suggested by regulatory bodies and health institutions, the following stand out: review of care flows and protocols; reinforcement of international patient safety goals, such as hand and hand hygiene and effective communication; use of quality indicators; team training; managerial actions; creation of crisis committees; health education and other innovative initiatives. Final considerations: the pandemic reinforces the importance of patient safety and rescues actions and strategies for safe and quality care, as well as overcoming emerging challenges.